A Study on The Factors That Influence the Acceptance of LMS’s In Higher Educational Institution’s - Ashish, Ashish (International Journal of Computer Sciences and Engineering, 2025)
This study is designed to investigate the acceptance of Learning Management Systems (Moodle) in Higher Educational Institutions (HEI’s) of Oman. Due to the technological developments the importance of using learning Management system in Higher Educational Institutes (HEI’s) are increasing day by day. This study is to investigate the acceptance of Learning Management Systems in different HEI’s of Sultanate of Oman. To investigate the factors that influence the use of LMS’s in HEI’s the 5-point likert questionnaire has been made and distributed electronically through e-mail and Social media applications. The questionnaire sent to the students of different HEI’s of Sultanate. Data were collected from 137 respondents belongs to various HEI’s in which 132 are the valid responses. The questionnaire consists of 5 demographic question and 13 survey questions. The variables used in this research are perceived playfulness, perceived usefulness, and perceived ease of use, attitude, and intention to use. The research is based on the Technology Acceptance Model (TAM). The Structural equation modelling (SEM) technique is used to evaluate the causal model and to extreme the validity of model. This research paper tested the 7 hypotheses